Evaluation of Avocado Peel Biochar for Methyl Orange Adsorption - Unlu, Ilayda Dilara; Kocer, Anil Tevfik; Inan, Benan; Ozcimen, Didem (Mehmet Sinan Bilgili, 2022)
Adsorption is one of the most effective, cheapest and easiest methods used in wastewater treatment. In this method, pollutants such as dyes and heavy metals called adsorbate, are separated from the aqueous environment and adsorbed to the surface of materials called adsorbent. In this process, the selection of materials to be used as adsorbent is very important. The surface area of these materials should be large and porous, and the material should be inexpensive and easily available. In this context, biomass wastes which have high potential for usage in industrial applications, are very suitable sources for adsorbent production. In this study, the potential of using biochars produced from avocado peel waste at different temperatures in methyl orange removal was investigated. In the first stage of the study, biochar production from avocado peel was carried out under different temperature conditions (400, 500 and 600 degrees C), and the characterization of the obtained biochars was performed. In the second stage, avocado peel biochars were used for methyl orange adsorption and adsorption kinetics were determined. As a result of the study, while the highest methyl orange removal was achieved using biochars produced at 600 degrees C; the lowest methyl orange removal was determined using raw avocado peel. According to these results, it was seen that biochars produced from avocado peel are quite suitable to be used as adsorbent. It can be reported that, the methyl orange removal efficiency can be improved by optimizing the production of avocado peel- based adsorbents and the adsorption process.
Keywords: Avocado peel; biochar; adsorption; methyl orange; AQUEOUS-SOLUTIONS; DYES; REMOVAL; Engineering; Environmental Sciences & Ecology